Konstruksi Pendidikan Karakter Sebuah Konsep Dan Model Terhadap Siswa Full Day School Di Era Pandemi Covid-19 - Kholidi, Ahmad Khaerul; Saparwadi, Saparwadi (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2021)
The Indonesian government is faced with a health crisis, this has an impact on new policy programs that have had an impact both in economic, political, cultural crises, and most prominently in the education sector. Millions of students feel anxious in studying, the solutions offered are not satisfied for every student. The Covid-19 pandemic has made this nation again faced with a moral crisis, a crisis of character, a crisis of honesty, even a crisis in every sector, therefore the role of education should be able to overcome the moral decline that befell students. Moral decline is a form of the crisis of the character of the students.The crisis of character reflects the failure of the education system implemented in every school, so that recently there have been a lot of complaints from parents, education, and people working in the religious and social fields, regarding the behavior of teenagers who are difficult to control, naughty, stubborn, do trouble, immoral brawl, get drunk, binge on drugs, live like hippies in Europe and America, and even commit piracy, rape, and murder. The function and role of education in building character is very much needed in the era of globalization and modernization. Education should be oriented towards building the character of students. This is necessary in order to develop and strengthen noble qualities to be tough, honest, virtuous, responsible, disciplined, and independent, but seeing the character crisis that has occurred proves that the education system has not formed the expected human resources.